Mental Health and Well-Being of University Students: A Bibliometric Mapping of the Literature - Hernández-Torrano, Daniel; Ibrayeva, Laura; Sparks, Jason; Lim, Natalya; Clementi, Alessandra; Almukhambetova, Ainur; Nurtayev, Yerden; Muratkyzy, Ainur (Frontiers in Psychology, 2020)
The purpose of this study is to map the literature on mental health and well-being of university students using metadata extracted from 5561 journal articles indexed in the Web of Science database for the period 1975-2020. More specifically, this study uses bibliometric procedures to describe and visually represent the available literature on mental health and well-being in university students in terms of the growth trajectory, productivity, social structure, intellectual structure, and conceptual structure of the field over 45 years. Key findings of the study are that research on mental health and well-being in university students: (a) has experienced a steady growth over the last decades, especially since 2010; (b) is disseminated in a wide range of journals, mainly in the fields of psychology, psychiatry, and education research; (c) is published by scholars with diverse geographical background, although more than half of the publications are produced in the US; (d) lies on a fragmented research community composed by multiple research groups with little interactions between them; (e) is relatively interdisciplinary and emerges from the convergence of research conducted in the behavioral and biomedical sciences; (f) tends to emphasize pathogenic approaches to mental health (i.e., mental illness); and (g) has mainly addressed seven research topics over the last 45 years: positive mental health, mental disorders, substance abuse, counseling, stigma, stress, and mental health measurement. The findings are discussed, and the implications for the future development of the field are highlighted.